Heteropoly Acid Catalyzed Selective Cyclization of 6-Alkyl-3-propargylmercapto-1, 2, 4-triazin-5(2H)-one. Issue 2 (2011) - Hakim, Fatemeh; Tabatabaee, Masoumeh; M. Hheravi, Majid; Roshani, Mina; F. Bamoharam, Fatemeh
Abstract : Cyclization of 6-alkyl-3-propargylmercapto-1, 2, 4-triazin-5(2 H )-one, derivatives (2) in the presence of Keggin heteropoly acids, H3 PW12 12O40, H3 PMo12 O40, H4 SiW12 O40 and lacunary Keggin structure (K7 PMo2 W9 O40 ) afforded 3 (3a = 6-dimethyl-7 H -thiazolo[2, 3-b][1, 2, 4]-triazin-7-one and 3b=6-ethyl-3-methyl-7 H -thiazolo[2, 3-b][1, 2, 4]-triazin-7-one) in high yields and short reaction times